Dynamic Distribution of Rail Potential with Regional Insulation Alteration in Multi-Train Urban Rail Transit - Ziyuan Kang; Guifu Du; Yaoda Xia; Qiaoyue Li; Guilu Zhang; Xin Guo; Weiguo Huang; Zhongkui Zhu (IET Electrical Systems in Transportation)
Rail potential (RP) has become a disaster for the safe operation of metro lines. In urban rail transit (URT), regional insulation degradation often occurs due to the harsh environment of the reflux conductor for traction current, leading to the complex distribution of RP. In this paper, the dynamic distribution of RP with regional insulation alteration in URT is studied. First, the distribution model of the reflux system with regional insulation alteration is established. Second, utilizing the distributed parameter element method and taking into account the constraint conditions of the concentrated parameters, a superposition calculation method of RP in the reflux system is proposed. Finally, using Guangzhou Metro as an example, the simulation of different insulation states in long and local areas of URT is carried out. Results show that the RP amplitude decreases while the stray current amplitude increases when the insulation is degraded. At the same time, when the insulation in the local area degrades, the RP at the far end increases.